Narrative Imagination of Islam in Nusantara: A Study on Islam in Babad Tanah Jawi and Babad Giyanti - Achmad Fawaid; Wening Udasmoro; Sri Margana; Miftahul Huda (UIN Raden Mas Said Surakarta, 2023)
The lack of research on literary elements in